Patient perception of voxelotor treatment benefit in sickle cell disease. (22nd June 2022) - Idowu, Modupe; Haque, Anam; Williams, Elisa M; Sridhar, Arthi
Abstract : Patients with sickle cell disease (SCD) experience a range of clinical symptoms, including acute and chronic pain, fatigue, and respiratory problems, as well as chronic organ complications that can lead to disability and accelerated mortality. Voxelotor is a first-in-class therapy that targets sickle hemoglobin polymerization, the root cause of SCD. It is approved by the US Food and Drug Administration for treatment of SCD in patients aged 4 years and older and in the European Union and United Arab Emirates for the treatment of SCD in patients aged 12 years and older. Here, we report the single-center experience of both clinician-determined and patient-reported benefits of voxelotor in 27 consecutive patients treated for at least 8 weeks. Clinical Global Impression of Change and Patient Global Impression of Change rating scales were used to capture clinicians' and patients' perceptions of change in overall patient health-related quality-of-life with voxelotor treatment. Laboratory data were also collected to assess clinical response to treatment. As observed in previous clinical studies, hemoglobin concentrations and markers of hemolysis were improved in patients treated with voxelotor. Most patients reported marked improvement in disease symptoms, which correlated well with the clinicians' assessments. Although limited by the retrospective open-label study design, these findings suggest that voxelotor use has a positive impact on outcomes in patients with SCD.